The "Egalitarian Ideal" and the Distribution of Wealth in the Northern Agricultural Community: A Backward Look - Atack, Jeremy; Bateman, Fred (The Review of Economics and Statistics, 1981)
This paper contributes new evidence on the wealth distribution in the rural North on the eve of the Civil War,' evidence which shows a greater degree of egalitarianism among a large segment of the population than have other studies. We argue that the wealth distribution in this particular historical economy may be used as a yardstick against which contemporary distributions might be judged. We also present evidence on the demographic and social characteristics of various groups of wealthholders and posit a causal chain from these characteristics to the concentration of wealth. To the extent that contemporaries asserted that the rural, free northern states were an egalitarian society, a study of the nature, extent and sources of economic inequality in that environment might demonstrate what is realizable as a policy objective in contrast to the Lorenzian goals or even the new standard recently proposed by Morton Paglin (1975 and 1977). Traditionally, historical analyses of egalitarianism in the nineteenth-century United States have focused on the distribution of wealth in two areas where it was least likely to be manifest, the slave-South and the urban centers.2 Our focus, however, is upon that segment of the population among which wealth, historically, was felt to have been most equally distributed: the nineteenth century rural North, an area that has received little attention despite its importance. Even where the rural North has been studied, as by Main (1976) or Newell (1977), the focus has been on narrowly defined geographic areas. The figures reported in table 1 present measures of the distribution of wealth for that group.